2014
DOI: 10.1590/s0100-69162014000300022
|View full text |Cite
|
Sign up to set email alerts
|

Control of ammonia emissions in naturally ventilated dairy cattle facilities in Portugal

Abstract: ABSTRACT:We conducted a study of the processes associated to NH 3 emission in naturally ventilated dairy cattle facilities, having described factors that regulate NH 3 emission, as well as methodologies for measuring these emissions at these facilities. Appropriate techniques to mitigate NH 3 emission in facilities located in regions with warm climates were also identified. The most effective mitigation techniques with simple implementation include strategies associated to: (i) installation design and flooring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…The length of the wind tunnel is 6.0 m. The wind tunnel is made of chemically stable material: stainless steel. The temperature and humidity of the air entering and leaving the manure chamber were measured with temperature and humidity sensors (8) connected to the Almemo 2590-9 system (14). Measuring range: temperatures from −30 to 60 °C; relative humidity from 5 to 98%; accuracy of the device ±0.1%.…”
Section: Research Methodology In Laboratory Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The length of the wind tunnel is 6.0 m. The wind tunnel is made of chemically stable material: stainless steel. The temperature and humidity of the air entering and leaving the manure chamber were measured with temperature and humidity sensors (8) connected to the Almemo 2590-9 system (14). Measuring range: temperatures from −30 to 60 °C; relative humidity from 5 to 98%; accuracy of the device ±0.1%.…”
Section: Research Methodology In Laboratory Conditionsmentioning
confidence: 99%
“…In the German livestock industry, most ammonia is emitted in naturally ventilated barns [13]. This view is shared by researchers in other countries [14]: naturally ventilated dairy barns are one of the main sources of ammonia and greenhouse gas emissions to the atmosphere. It is difficult to clean the air in these barns.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally ventilated cattle barns pose many methodical issues for the analysis of gas emissions, no precise methods for measuring the gas spread are available, the ventilation rate is difficult to be found (Teye et al, 2008;Kaasik et al, 2013;Bleizgys et al, 2013). Researchers that have studied the microclimate in barns of this particular type have found that processes of NH3 emissions and air pollution are difficult to control there (Bjerg et al, 2013;Rzeznik et al, 2016;Samer et al, 2012;Pereira et al, 2014;Mendes et al, 2015;Zhao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The most common liquid manure handling systems for cows in Europe are scraping and flushing systems where a mixture of urine, faeces and litter materials (i.e., cattle slurry) are drained together from housing to manure storage facilities (Pereira & Trindade, 2014). Then, the cattle slurry stored is applied to land as organic fertiliser.…”
mentioning
confidence: 99%
“…Previous studies (Hristov et al, 2011;Pereira & Trindade, 2014) intensive dairy farm. On the other hand, the reduction of replacement animals (heifers) has a similar effect than high milk production per cow and could reduce NH 3 and GHG emissions in farms.…”
mentioning
confidence: 99%